Version control - Palmer, Dexter Clarence, 1974- (Pantheon Books, 2016)
The compelling story of a couple living in the wake of a personal tragedy. She is a star employee of an online dating company, while he is a physicist, performing experiments that, if ever successful, may have unintended consequences, altering the nature of their lives and perhaps of reality itself. Rebecca Wright has gotten her life back, finding her way out of grief and depression following a personal tragedy years ago. She spends her days working in customer support for the Internet dating site where she first met her husband. However, she has a persistent, strange sense that everything around her is somewhat off-kilter: she constantly feels as if she has walked into a room and forgotten what she intended to do there; on TV, the President seems to be the wrong person in the wrong place; and each night she has disquieting dreams that may or may not be related to her husband Philip's pet project. Philip's decade-long dedication to the causality violation device (which he would greatly prefer you do not call a time machine ) has effectively stalled his career and made him a laughingstock in the physics community. But he may be closer to success than either of them knows or imagines . . .